Analysis of Hyponymy in ‘Oliver Twist’ novel by Charles Dickens (1838): Semantics Study - Luthfiah Ammar Mufid; Ervina CM Simatupang (Budapest International Research and Critics University, 2022)
The aim of this study is to analyze the types and the functions of hyponymy used in Oliver Twist’s novel by Charles Dickens. In the books, Charles Dickens tells the life story of Oliver Twist that has a lot of moral stories in it. However, hyponymy is widely used in the novel as an explanation to the words so the readers can understand clearly about every word in the novel. The method used in carrying out the study was a descriptive qualitative method. Therefore, the results of this research that were taken from Oliver Twist, a children's novel by Charles Dickens (1838) are 38 data that are qualified as 5 types of hyponymies such as 10 data hyponymy of the body part (26%), 7 data of hyponymy object (18%), 9 data of hyponymy family (23%), 6 data of hyponymy feelings (15%), and 5 data of hyponymy of buildings (13%) as the least frequent relation in the novel.